One‐Pot Synthesis of Phosphanylbis(N‐arylglycines) and Spontaneous Diastereoselective Lactamization of P‐Alkyl Derivatives To Form Five‐Membered P, N‐Heterocyclic Amino Acids. Issue 21 (27th June 2016) - Lach, Joanna; Palm, Gottfried J.; Jones, Peter G.; Heinicke, Joachim W.
Abstract : The one‐pot, three‐component reaction of phenylphosphane with two equivalents each of 4‐acetylaniline and glyoxylic acid hydrate (GAH) in diethyl ether at room temperature furnished phosphanyl‐bis(glycine)1 as a rac/meso mixture (molar ratio 7:3) whereas condensation of primary alkylphosphanes ( c HexPH2, i BuPH2 ) with p ‐toluidine and GAH was followed by additional spontaneous and highly diastereoselective lactamization to form five‐membered P, N‐heterocyclic racemic amino acids2 and3 . Compound2, with three centres of asymmetry, displayed only one set of NMR signals, whereas for compound3 one set was strongly preferred. Crystal structure analysis of2 confirmed the presence of a racemate, with the asymmetric unit consisting of the 2 R, 3 R, 4 R isomer; the molecules are linked by hydrogen bonds. The trans(eq‐eq) ‐position of the P ‐cyclohexyl group towards the substituents at the adjacent C2 and C4 atoms is maintained in [D8 ]THF solution, as shown by small 2 J PH coupling constants. Large 2 J PH couplings in compound3 hint at the opposite preference, i.e. cis orientation, of the less spatially demanding isobutyl group at phosphorus towards the C2 and C4 substituents. The trans isomers of3 were detected only in trace amounts on the basis of characteristic PCH proton doublets with small 2 J PH values. This facile route to novel trialkylphosphane‐type hybrid ligands2 and3 may pave the way for further studies of their properties and use as ligands in transition metal compounds and catalysis. Abstract : PhPH2 reacts with glyoxylic acid hydrate and a primary aniline (1:2:2) in Et2 O to afford a rac/meso ‐mixture of corresponding phosphanyl‐bis(glycine)1 . Under the same mild conditions, more P ‐basic primary alkylphosphanes CyPH2 and i BuPH2, undergo diastereoselective lactamization affording phosphaproline derivatives2 and3 ; the structure of2 was amenable to X‐ray crystallography.